Study of the Weights and Dimensions of the Body in the Iraqi Awassi Sheep (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
This study was undertaken at the native feilds of the sheep farms in Sadet Al-hindia, Babylon Governorate, over period from December 2017 to March 2018. The aim of this was  study the effect of type of birth and sex of lambs on the traits of birth and weaning weight, body dimensions(body length, chest circumference, height at the front and back)in awassi sheep. the results showed that significant superiority (p˂0.05) for twins lambs (40.9cm) on single lambs(39.33cm)  in body length at the birth .for the sex of lambs, male lambs has significant superiority (p˂0.05) on female lambs in heightin front (41.03,40.07 cm Respectevly), but the type of birth and sex of lambs had nonsignificant effect of other parameters .